Post-injury fear-a voidance and confidence in readiness to return to sport in Irish collegiate athletes - O`Connor, S.; Moloney, A.; Beidler, E.; Whyte, E.; Moran, K.; Teahan, C.; Farrelly, M. (Journal of Sports Sciences, 2022)
Fear avoidance and low confidence in their ability to return to sport can impede athletes` subsequent recovery and return to sport. This study aimed to identify fear avoidance and confidence in readiness to return to sport following injury in Irish collegiate athletes. Male (416) and female (256) athletes from 24 field-sport teams at one university were prospectively followed for one season. The Athlete Fear Avoidance Questionnaire (AFAQ) and pain on the Visual Analogue Scale was completed following a time-loss injury. Prior to return to sport, participants completed the AFAQ and the Injury Psychological Readiness to Return to Sport (I-PRRS). We recorded 179 injuries. Fear avoidance was evident post-injury (21.8 ± 6.7), and the mean total I-PRRS score was 48.4 ± 8.9. Those with severe injuries presented with higher fear avoidance and lower confidence. Higher pain was associated with greater fear avoidance following injury (r = 0.32, p < 0.0001), prior to return to sport (r = 0.38, p < 0.0001), and with lower confidence (r = -0.27, p < 0.0001). Low confidence and fear avoidance was identified, particularly in those with a severe injury or high pain levels. Identifying, and providing psychosocial support to athletes experiencing, these issues is recommended.